Influence attitude homophily and social attractiveness to purchase intention with parasocial relationship as an intervening variable in Erigo - Naufal, Hafizh Eki; Dewi, Citra Kusuma (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to examine the impact of attitude homophily and social attractiveness on purchase intention, with parasocial relationships serving as an intervening variable in the local fashion brand Erigo. This study employs a quantitative approach with an explanatory design to investigate the causal relationships between attitude homophily, social attractiveness, parasocial relationships, and purchase intention among Erigo customers via an online poll of @erigostore Instagram followers. A purposive sampling strategy was used to select 400 respondents based on specific criteria, and data were collected via a Likert scale-based questionnaire. Data were analyzed using the PLS-SEM approach with SmartPLS, which included measurement model testing (validity and reliability) and structural model testing. The results showed that attitude homophily and social attractiveness of influencers significantly influence the formation of parasocial relationships with audiences. Strong parasocial relationships are shown to increase consumers’ purchase intentions toward recommended products. Similarity of values and social attractiveness strengthen emotional attachments that drive trust and purchase decisions. The practical implication is that companies need to select influencers who are able to build emotional closeness and have social attractiveness that matches the target audience to optimize digital marketing strategies.